Water quality assessment in wet season of Langat River, Selangor, Malaysia - Muhammad Amir Danish; Tay, Chia Chay; Muhammad Izzat Nor Ma’arof; Girma T. Chala; Nurul Fariha Lokman (Penerbit Universiti Kebangsaan Malaysia, 2024)
Water quality assessment is crucial for human and environmental health, but studies often face challenges with missing or incomplete data across seasons. This study evaluated the water quality of the Langat River in Selangor, Malaysia, during the wet season, focusing on Water Quality Index (WQI), water classification, and trace metal concentrations. The WQI model, used by Malaysia’s Department of Environment (DOE), serves as a tool for assessing water quality. Water samples were taken from three sites: Kampung Hulu Kuala Pansoon (upstream), Pekan Bt 18 (midstream), and Nanding (downstream). Results showed significant water quality degradation from upstream to downstream, with WQI of 88.01 (Class II) at Kampung Hulu Kuala Pansoon, while both Pekan Bt 18 and Nanding fell into Class III with WQI of 76.50 and 71.68, respectively. While Class II indicates clean water, Class III reflects slightly polluted conditions based on the National Water Quality Standard (NWQS). Population density and land use types were identified as factors in this decline. Trace metal analysis as arsenic, chromium, cadmium, lead, aluminum, zinc, and manganese were present downstream. Although most levels were below NWQS limits, aluminum at 0.071mg/l exceeded permissible values, and manganese 0.09 mg/l detected to be close to the allowable threshold. The small dataset limits accuracy but adds insight to water assessment in wet season. Future studies need more sampling locations and hydrological data. In supporting SDG 6, continuous collaboration with state authorities aims to prevent degradation, ensure Class IIA compliance, and protect water supplies for Selangor’s Water Treatment Plants.